Coordinated Morphogenetic Mechanisms Shape the Vertebrate Eye - Martinez-Morales, Juan-Ramon; Cavodeassi, Florencia; Bovolenta, Paola (Frontiers in Neuroscience, 2017)
The molecular bases of vertebrate eye formation have been heavily investigated during the past twenty years. This has resulted in the definition of the backbone of the gene regulatory networks controlling the different steps of eye development and has further highlighted a substantial conservation of these networks among vertebrates. Yet, the precise morphogenetic events allowing the formation of the optic cup from a small group of cells within the anterior neural plate are still poorly understood. It is also unclear if the morphogenetic events leading to eyes of very similar shape are indeed comparable among all vertebrates or if there are species-specific peculiarities. Improved imaging techniques have enabled to follow how the eye forms in living embryos of a few vertebrate models, whereas the development of organoid cultures has provided fascinating tools to recapitulate tissue morphogenesis of other less accessible species. Here, we will discuss what these advances have taught us about eye morphogenesis, underscoring possible similarities and differences among vertebrates. We will also discuss the contribution of cell shape changes to this process and how morphogenetic and patterning mechanisms integrate to assemble the final architecture of the eye.